The politics of money - Johnson, Brian D. G. (London : J. Murray, 1970)
This book is about the listening aspect of money. It pointed out that money does not listen to the individual but to the actions of government and the community as a whole. It is not about the spending of money, but who or what influences money's buying power when it is spent; and it is about the effect that changes in money's value have upon the distribution of wealth and power.
Includes index
Bibliography: p. 321-330.
usc 12/04/18
Loans
Keywords: Monetary policy; International finance; Balance of payments; Great Britain